Estimation Carbon Stocks of Mangrove Stands in Nagari Pilubang, Sungai Limau District, Padang Pariaman Regency - Afriona, Nada; Putri, Irma Leilani Eka (Jurnal Serambi Biologi, 2024)
Mangrove ecosystems are one of the ecosystems that play a role in reducing carbon emissions in the air and storing carbon from the air in the form of biomass. Research on the estimation of carbon stocks is needed to support climate improvement in the world due to global warming. The purpose of this study was to determine the estimated amount of carbon stocks of mangrove stands in Nagari Pilubang, Sungai Limau District, Padang Pariaman Regency. The method used is purposive sampling carried out at three stations with varying mangrove ecosystem conditions. Each research station is divided into three research plots. To calculate the value of stand biomass used allometric equations, carbon stock estimates are obtained from the value of mangrove stand biomass. Based on the results of the study, it is known that the estimated amount of carbon stocks of 5,704.11 tons / ha is categorized as high.